The Tentacular Strike Behavior in Squid: Functional Interdependency of Morphology and Predatory Behaviors During Ontogeny - Vidal, Erica A. G.; Salvador, Bianca (Frontiers in Physiology, 2019)
This study examines the relationship between morphology and predatory behaviors to evaluate the ontogeny of the specialized tentacular strike (TS) in Doryteuthis opalescens squid reared under laboratory conditions (hatching-80 day-old; 2-16 mm mantle length-ML). Ontogenetic morphological changes in the arm-crown and the role played by the arms and tentacles during predatory behavior was correlated with prey types captured and revealed interconnected morphological and behavior traits that enabled paralarvae to perform the TS. Hatchlings have a poorly-developed arm-crown and tentacles that resemble and function as arms, in which tentacular clubs (suckerfull non-contractile portion) and stalks (suckerless contractile portion) have not yet formed. Only a Basic Attack (BA) behavior was observed, involving arms and tentacles, which were not ejected during prey capture. A more elaborated behavior, the Arm-net (AN) was first employed by 30 day-old (>4.7 mm ML) paralarvae, in which the tentacles were eject down, but not towards the prey. The TS was first observed in 40-50 day-old (6.7-7.8 mm ML) squid, which stay stationary by sustainable swimming prior to ejecting the tentacles towards the prey. Thus, the ability to perform sustainable swimming and acquisition of swimming coordination (schooling behavior) are prerequisites for the expression of the TS. The arms played the same roles after prey was captured: hold, subdue and manipulate the prey, while the actions performed by the tentacles truly defined each behavior. Prey size captured increased with increasing squid size. Morphometric data showed that hatchlings have little ability of elongating their tentacles, but this ability increases significantly with size. Squid older than 40 days could elongate their tentacles up to 61% of their ML, whereas early paralarvae 13% on average. Paralarvae were frequently observed elongating and contracting their tentacles, while not attempting to capture prey, which could perhaps serve to adjust muscle activity and development, while specializations for the strike – stalks, clubs, muscle fibers, arm-crown and swimming coordination – are still being developed. The expression of the TS is constrained by development in early paralarvae as it involves interdependency of morphology and behavior and as such, represents a major developmental milestone in the early-life history of squid.